Can supply chain initiatives reduce deforestation? A comparative analysis of cases from Brazil and Indonesia - Karen Meijer (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
Deforestation and forest degradation account for 12-15% of global greenhouse gas emissions. The largest driver of deforestation is the conversion of land for agriculture, the produce of which is for a large part traded internationally. In the absence of formal regulations, private sector initiatives have been established to reduce deforestation in supply chains. It is important to understand to what extent these supply chain initiatives can effectively reduce deforestation in order to develop public policies at national or international level that can facilitate or complement the private initiatives. This discussion paper contributes to addressing this issue by analysing the functioning of supply chain initiatives to reduce deforestation. The paper presents a framework of factors influencing the effectiveness of voluntary supply chain initiatives based on the literature available. Using this framework, four supply chain initiatives to reduce deforestation for major commodity production are qualitatively assessed and compared for their functioning in the context of a specific country. These initiatives are: the Roundtable on Sustainable Palm Oil (RSPO) in Indonesia, the Roundtable on Responsible Soy (RTRS), the Soy Moratorium and the Cattle Agreement (all three in Brazil). The RSPO and RTRS are certification schemes, to which farmers can voluntarily comply in exchange for the possibility of receiving a price premium or of selling credits. The Soy Moratorium and Cattle Agreement are moratoria, to which compliance by farmers is also voluntary, but where non-compliance would result in being taken off the list of suppliers of major processers and traders. Compared to certification schemes, the two moratoria have stricter and clearer criteria regarding the reduction of deforestation, which allow for monitoring and enforcement and low leakage (the displacement of deforestation to other areas, or by others) within the area under the moratorium (in this case the Amazon). The moratoria have had high implementation rates, resulting from the dependence of farmers on the parties who established the moratorium. While demand for sustainable products is often considered the major driving force for more sustainable production, in the case of soy, this demand was not sufficient to lead to high adoption of the RTRS standard. At the same time, the reputational risk that large soy processers and traders perceived when being exposed by NGOs, has effectively led to a reduction in deforestation in the Amazon region. The high effectiveness of the moratoria has been attributed to the combined activities of NGOs, supply chain actors, national governments and international governments. The two certification schemes both contain ambiguous criteria, banning the clearance of certain types of forest, which cannot be unambiguously assessed and may lead to the clearance of other forest areas which are also important from a climate and biodiversity perspective. Different reasons are given for the low implementation of the certification schemes: Brazilian soy producers appear to think that existing laws suffice, while for the RSPO the low price premium may be the reason for low compliance. It is not clear in any of the initiatives what the technical and institutional possibilities are for farmers to expand production with reduced or no deforestation and, in relation to this, what the costs and incentives are to comply. Leakage remains a major risk related to voluntary supply chain initiatives. Supply chain initiatives can only be effective if they have high sector participation and full spatial coverage. Demand for sustainable production is important, although exposure seems to have been key for the moratoria. Technical and institutional possibilities for farmers to expand production without deforestation or with reduced deforestation are not well understood. It is important to understand the individual decisions at the various different levels in order to develop public policies that can facilitate or complement the supply chain initiatives.
Keywords: 330; Klimawandel; Landwirtschaft und ländliche Entwicklung